Investigating “Hidden side” of Foreign Language Teacher: Cognition, Affect, and Motivation - Jandildinov, M.K.; Kashkinbayeva, Z.Zh.; Dergunova, Ye.Yu.; Yersultanova, G.T. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The primary aim of this study is to investigate “hidden side” of foreign language teacher. In order to describe foreign language teacher such factors as Cognition, Affect, and Motivation were taken and investigated. The study used English language teachers in order to investigate “Foreign language teacher”. The research sample consists of 40 English language teachers working in different public schools from different cities, teaching levels and various ages and work experiences in Kazakhstan. In order to describe general portrait of foreign language teacher Professional orientation method was used. According to the results, English language teachers have three professional orientations: Self-orientation, Communication-orientation, and Task-orientation. Based on these orientations cognitive, affective, and motivational sides of the teachers were described and compared. The results provide detailed comparison and description of English language teachers with respect to cognition towards communicative approach, motives to work and emotions about teaching English at schools.
Шет тілі мұғалімінің «жасырын жағын» зерделеу: таным, ықпал және мотивация
Изучение «скрытой стороны» учителя иностранного языка: познание, влияние и мотивация
Keywords: hidden side; English language teacher; teacher profile; teacher cognition; teacher affect; teacher motivation